Bringing meaning to user involvement in mental health care planning: a qualitative exploration of service user perspectives. Issue 1 (3rd December 2015) - Grundy, A. C.; Bee, P.; Meade, O.; Callaghan, P.; Beatty, S.; Olleveant, N.; Lovell, K.
Accessible summary: What is known on the subject?: UK mental health policy dictates user involvement in mental health care planning. Service users report feeling marginalized in the care planning process. Ongoing dissatisfaction with care planning involvement suggests a failure to translate policy into practice over time. What this paper adds to existing knowledge?: Service user involvement should no longer be regarded as a nebulous concept. Ten key criteria underpin service user satisfaction with care planning involvement. Five criteria characterizing the process of care planning involvement are prioritized by service users. What are the implications for practice?: Service users can conceptualize and describe meaningful user involvement. Service user requests, summarized through a 10C framework of care planning involvement, provide a clear structure for practice improvement. Abstract: Background: Service users wish to be involved in care planning but typically feel marginalized in this process. Qualitative explorations of the barriers and enablers of user involvement in mental health care planning are limited. Question: How is user involvement in care planning conceptualized by service users and how can meaningful involvement be instilled in the care planning process? Methods: In 2013, we conducted five focus groups ( n = 27) and 23 individual interviews with current or recent adult users of secondary care mental health services ( n = 27) in England. Eight users participated in both. Data were analysed using Framework Analysis. Results: Ten themes emerged from the data: these themes encompassed procedural elements (connection; contribution; currency; care consolidation; and consequence), service user characteristics (capacity and confidence) and professional enablers (consultation; choice; and clarity of expression). Procedural elements were discussed most frequently in service user discourse. Discussion: The process of care planning, centred on the user‐clinician relationship, is key to user involvement. Implications for Practice: Users describe a common model of meaningful involvement in care planning. Their requests, summarized through a 10C framework of care planning involvement, provide clear direction for improving service users satisfaction with care planning and enhancing the culture of services.